Three essays on the effectiveness of financial education in the workplace - Horwitz, Edward J. (Kansas State University, 2015)
Retirement savings and income projections are among the most financially complex calculations individual Americans will encounter. The movement towards self-directed employer retirement plans has shifted the responsibility for securing an adequate retirement increasingly to the employee, who may lack the financial understanding needed for proper calculations and decisions. There is an expressed preference among employees for the delivery of financial education in the workplace, where a majority of their financial knowledge is obtained. However, adoption of workplace comprehensive financial education programs has been slow due to the cost, time commitment, and lack of empirical support for their value. While there have been some mixed findings, literature has generally supported associations between financial education programs and improved literacy and behaviors. A great deal of these mixed results can be explained by the lack of consistency among definitional frameworks for financial literacy, the lack of consistent measures, and the variety of topics and methods used, all of which limit the ability to establish causal support for the educational program’s effectiveness. However, the preference for financial education in the workplace among employees suggests both the need and desire for more comprehensive financial education offered by employers. The purpose of this research was to investigate and test the links between the components in the framework for financial literacy by testing participation in a worksite comprehensive financial education program. In Essay One, the link between financial education and change in financial literacy was tested. Essay Two tested the link between the financial education program and financial well-being. In Essay Three, the link between financial literacy and financial behavior was explored. The results indicated associations between all three links in the financial literacy model, utilizing both primary research employing quasi-experimental methods, and secondary research from a larger national data sample. For financial educators who are interested in developing and facilitating comprehensive financial education programs for employee or other groups, this research can help provide support and guidance for those efforts. If comprehensive financial education programs can be better positioned to help improve the levels of financial literacy among Americans, fewer negative associated behavioral effects, such as lack of planning and under saving for retirement, may occur.
Keywords: Financial literacy; Financial education; Financial well-being; Education Finance (0277)